Platypnea-Orthodeoxia Syndrome: A Case of Persistent Hypoxemia in an Elderly Patient. Issue 5 (3rd August 2021) - Ribeiro, Renata; Fialho, Inês; Boavida, Leonor
Abstract : Supplemental Digital Content is available in the text.